2007
DOI: 10.1093/hmg/ddm059
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis-1 (Nf1) heterozygous brain microglia elaborate paracrine factors that promote Nf1-deficient astrocyte and glioma growth

Abstract: The tumor microenvironment is considered to play an important role in tumor formation and progression by providing both negative and positive signals that influence tumor cell growth. We and others have previously shown that brain tumor (glioma) formation in Nf1 genetically engineered mice requires a microenvironment composed of cells heterozygous for a targeted Nf1 mutation. Using NF1 as a model system to understand the contribution of the tumor microenvironment to glioma formation, we show that Nf1+/- brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 62 publications
10
163
0
Order By: Relevance
“…More specifically, Ptprd +/− p16 −/− tumors had activated genes involved in up-regulation of several chemokines, all of which promote M2 polarization (23)(24)(25)(26). Macrophages can enhance tumor cell survival by promoting tumor growth, invasion, or immunosuppression (27)(28)(29)(38)(39)(40). In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Ptprd +/− p16 −/− tumors had activated genes involved in up-regulation of several chemokines, all of which promote M2 polarization (23)(24)(25)(26). Macrophages can enhance tumor cell survival by promoting tumor growth, invasion, or immunosuppression (27)(28)(29)(38)(39)(40). In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…Results from in vitro studies support the idea that microglia can promote tumor invasion and growth (Bettinger et al, 2002;Markovic et al, 2005). Perhaps the most convincing evidence of the importance of microglia to glioma formation is from in vivo studies that have shown that tumor cell growth is inhibited in microglia-deficient glioma mouse models (Daginakatte and Gutmann, 2007;Markovic et al, 2009). These findings suggest that therapies that target glioma-associated microglia may be promising antitumor agents.…”
Section: Microgliamentioning
confidence: 85%
“…There are several cell types that make up the tumor stroma and can contribute to the biology of glioma to include astrocytes, endothelial cells, pericytes and cells involved in the immune response (that is, microglia and T-lymphocytes; Daginakatte and Gutmann, 2007;Charles et al, 2011). The tumor microenvironment is enriched with soluble factors secreted by these cells.…”
Section: Glioblastomas Are Molecularly Heterogeneous Tumorsmentioning
confidence: 99%
“…The cells that mainly contribute to the supportive effect of the glioma microenvironment on glioma progression are tumor-associated microglia/macrophages (TMMs) [5][6][7][8] .…”
Section: Research Highlightmentioning
confidence: 99%
“…It is now well established that the tumor microenvironment supports glioma progression [6][7][8][9][10][11] . Thus the ineffectiveness of the current treatments may result, at least in part, from their inability to suppress the tumor microenvironment's supportive effect.…”
mentioning
confidence: 99%